The mechanism of functioning the municipal-industrial system for management of social development of a city - V. A. Cvetkov (Путеводитель предпринимателя)
For more effective and high-quality management of social development of an industrial city is necessary to form municipal-industrial system for management of social development of a city; the mechanism of collaboration between local government and large industrial factories is core and driving force of this system, it has built on base of sustainable resources exchange and sustainable social capital.